Pendeteksian Hubungan Rating Hotel Terhadap Okupansi Hotel Pasca Pandemi Covid-19 - Yustiani, Dwi; Nooraeni, Rani; Lumaksono, Adi (Jurnal Kajian Pariwisata, 2023)
After the Covid-19 pandemic, Bali tourism began to revive, marked by an increase in hotel occupancy. Digitalization is playing its part in improving tourism in general. This study aims to look at hotel occupancy profiles in the Sarbagita and Non Sarbagita areas and to see how high digital hotel ratings are in the two areas. This study also detects a relationship between hotel ratings and hotel occupancy in the two regions. The data used in this study are VHTS data for 2019 and 2022 sourced from the Central Bureau of Statistics, as well as hotel rating data by utilizing big data. with web scraping technique. This study used descriptive statistics and inferential statistics using the Chi Square test. The research results obtained were changes in hotel occupancy patterns in the Sarbagita area which tended to increase in December after the Covid-19 pandemic. The Chi-Square test shows that there is a relationship between hotel ratings and hotel occupancy for both the Sarbagita and non-Sarbagita areas.